Phylogenetics of Lepidonotopodini (Macellicephalinae, Polynoidae, Annelida) and Comparative Mitogenomics of Shallow-Water vs. Deep-Sea Scaleworms (Aphroditiformia) - Avery S. Hiley; Nicolás Mongiardino Koch; Greg W. Rouse (Biology)
Within Polynoidae, a diverse aphroditiform family, the subfamily Macellicephalinae comprises anchialine cave-dwelling and deep-sea scaleworms. In this study, Lepidonotopodinae is synonymized with Macellicephalinae, and the tribe Lepidonotopodini is applied to a well-supported clade inhabiting deep-sea chemosynthetic-based ecosystems. Newly sequenced “genome skimming” data for 30 deep-sea polynoids and the comparatively shallow living Eulagisca gigantea is used to bioinformatically assemble their mitogenomes. When analyzed with existing scaleworm mitogenomes, deep-sea scaleworms exhibit increased gene order rearrangement events compared to shallow-water relatives. Additionally, comparative analyses of shallow-water vs. deep-sea polynoid substitution rates in mitochondrial protein-coding genes show an overall relaxed purifying selection and a positive selection of several amino acid sites in deep-sea species, indicating that polynoid mitogenomes have undergone selective pressure to evolve metabolic adaptations suited to deep-sea environments. Furthermore, the inclusion of skimming data for already known Lepidonotopodini species allowed for an increased coverage of DNA data and a representation of the taxa necessary to create a more robust phylogeny using 18 genes, as opposed to the six genes previously used. The phylogenetic results support the erection of Cladopolynoe gen. nov., Mamiwata gen. nov., Photinopolynoe gen. nov., Stratigos gen. nov., and Themis gen. nov., and emended diagnoses for Branchinotogluma, Branchipolynoe, Lepidonotopodium, and Levensteiniella.